A Key Intermediate in Copper‐Mediated Arene Trifluoromethylation, [nBu4N][Cu(Ar)(CF3)3]: Synthesis, Characterization, and C(sp2)−CF3 Reductive Elimination. (13th May 2019) - Lu, Zehai; Liu, He; Liu, Shihan; Leng, Xuebing; Lan, Yu; Shen, Qilong
Abstract: The synthesis, characterization, and C(sp 2 )−CF3 reductive elimination of stable aryl[tris(trifluoromethyl)]cuprate(III) complexes [ n Bu4 N][Cu(Ar)(CF3 )3 ] are described. Mechanistic investigations, including kinetic studies, studies of the effect of temperature, solvent, and the para substituent of the aryl group, as well as DFT calculations, suggest that the C(sp 2 )−CF3 reductive elimination proceeds through a concerted carbon–carbon bond‐forming pathway. Abstract : Stabile Cuprat(III)‐Komplexe [ n Bu4 N][Cu(Ar)(CF3 )3 ] wurden synthetisiert und charakterisiert, und ihre reduktive C(sp 2 )‐CF3 ‐Eliminierung wurde untersucht. Kinetische Studien, Untersuchungen der Auswirkungen von Temperatur und Lösungsmittel sowie DFT‐Rechnungen weisen darauf hin, dass die reduktive C(sp 2 )‐CF3 ‐Eliminierung eine konzertierte Bindungsbildung umfasst.